2019
DOI: 10.1101/561597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Src-dependent DBL family members drive resistance to vemurafenib in human melanoma

Abstract: The use of selective BRAF inhibitors (BRAFi) has produced remarkable outcomes for patients with advanced cutaneous melanoma harboring a BRAF V600E mutation. Unfortunately, the majority of patients eventually develop drug-resistant disease. We employed a genetic screening approach to identify gain-of-function mechanisms of BRAFi resistance in two independent melanoma cell lines. Our screens identified both known and unappreciated drivers of BRAFi resistance, including multiple members of the DBL family. Mechani… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 46 publications
(50 reference statements)
3
7
0
Order By: Relevance
“…The partial loss of RAC1 in the A375 shNT cells did not affect their sensitivity to vemurafenib in a 72h dose response assay ( Figures 7A,B and Supplementary Figure 5D). However, RAC1 knockdown increased sensitivity of these cells to vemurafenib (3 µM) exposure in a 5 day growth assay, consistent with previously reported results (19) (Figure 7C). In contrast, expression of the shRAC1#1 and shRAC1#2 constructs resulted in a moderate increase in vemurafenib sensitivity in A375 CUL3 KD cells with both assays ( Figures 7A-C and Supplementary Figures 5E,F).…”
Section: Rac1 Kd Partially Reverses Vemurafenib Resistance In A375 Cusupporting
confidence: 92%
See 1 more Smart Citation
“…The partial loss of RAC1 in the A375 shNT cells did not affect their sensitivity to vemurafenib in a 72h dose response assay ( Figures 7A,B and Supplementary Figure 5D). However, RAC1 knockdown increased sensitivity of these cells to vemurafenib (3 µM) exposure in a 5 day growth assay, consistent with previously reported results (19) (Figure 7C). In contrast, expression of the shRAC1#1 and shRAC1#2 constructs resulted in a moderate increase in vemurafenib sensitivity in A375 CUL3 KD cells with both assays ( Figures 7A-C and Supplementary Figures 5E,F).…”
Section: Rac1 Kd Partially Reverses Vemurafenib Resistance In A375 Cusupporting
confidence: 92%
“…Indeed, constitutively active mutant of RAC1 (RAC1 P29S ) is found in 10% of MAPKi progression melanoma tumors and overexpression of PAK may promote MAPKi resistance in some settings (9,10,(16)(17)(18). Based on our previous work showing that RAC-driven mechanisms of resistance can be ablated with the addition of the Src family inhibitor (Srci) saracatinib (19), we evaluated the effect of vemurafenib in combination with saracatinib. The drug combination decreased the level of pMEK S298 in both A375 NT and CUL3 KD cells compared to vemurafenib alone (Figures 4A,B) whereas it had no effect on pMEK S217 level (Figures 4A,C).…”
Section: Cul3 Kd Cells Are Sensitive To Vemurafenib + Srci Treatmentmentioning
confidence: 99%
“…Our data show that this is not due to on-target BTK inhibition, but is due to off-target inhibition, presumably of at least one SFK. Other studies have also identified a role for SFKs in BRAFi resistance (69)(70)(71), further supporting the idea that off-target anti-SFK activity of potential melanoma therapeutics may be mechanistically important. One study in particular characterized a novel dual RAF/SRC inhibitor which retains activity against melanoma tumors which had previously developed resistance to dabrafenib/trametinib therapy (72).…”
Section: Discussionmentioning
confidence: 64%
“…Our first application of this mutagenesis approach was to derive human melanoma cells resistant to the BRAF inhibitor vemurafenib (Fig.2) (Feddersen et al 2019). This screen identified nine candidate genes as drivers of vemurafenib resistance in A375 cells ( Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Of the nine genes identified by gCIS2, eight were predicted to drive resistance through over-expression and one was predicted to drive resistance via gene disruption ( Supplemental Table 1). Importantly, we have recently described experiments that functionally validated the role of four of these candidates (VAV1, MCF2, BRAF, RAF1) in driving vemurafenib resistance in human melanoma cell lines (Feddersen et al 2019). We next evaluated the eight genes predicted to drive vemurafenib resistance via over-expression, as determined by gCIS2.…”
Section: Functional Prediction Of Transposon Effects On Candidate Genesmentioning
confidence: 99%